Strategi Pemasaran UMKM Batu Permata Batu Di Desa Batu Asih, Kecamatan Cibadak, Kabupaten Sukabumi, Jawa Barat - Enny Istanti; Julyanto Ekantoro; RM Bramastyo KN (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
Through the integration of domestic, foreign, and international marketing activities that can create synergies while maintaining the organization's strategic objectives and competitive advantage as a force in global marketing efforts, global gold marketing acknowledges complex global (geocentric) market commonalities. This study (Study on MSMEs in Batuasih Village, Cibadak District, Sukabumi Regency) intends to ascertain how the marketing strategy of gemstone MSMEs in Batuasih village seeks to increase family income. Qualitative research methodology is the approach employed. The following are the MSME Marketing Strategy initiatives carried out by Batu Asih Village's gemstone artisans: Establishing groups for gemstone craftsmen, bolstering marketing teams, utilizing social media, becoming a member of fan clubs for gemstones, regularity in the content uploads for Gemstone products, Regular updating of content and enhancement of the product.